Pengaruh Kualitas Sistem dan Kualitas Pelayanan Terhadap Loyalitas Pengguna dengan Kepuasan Pengguna Sebagai Variabel Intervening Aplikasi Digital Korlantas pada Kantor Polisi Sektor Ciledug Kota Tangerang - Rizky Tarmudzi; Arief Wibowo (Economic Reviews Journal, 2026)
The digital transformation of public services requires government institutions, including the Indonesian National Police (Polri), to provide efficient and responsive technology-based services. The Digital Korlantas application is one of Polri’s initiatives aimed at facilitating online traffic-related services. However, low user satisfaction and loyalty—particularly in local sectors such as the Ciledug Police Sector, Tangerang City—indicate challenges in its implementation. This study aims to analyze the influence of system quality and service quality on user loyalty, with user satisfaction as a mediating variable. A quantitative approach was used with Partial Least Square Structural Equation Modeling (PLS-SEM) as the analytical technique. The sample consisted of 100 respondents who were users of the Digital Korlantas application within the jurisdiction of the Ciledug Police Sector. The results show that both system quality and service quality have a positive and significant impact on user satisfaction. Furthermore, user satisfaction significantly mediates the relationship between system and service quality and user loyalty. These findings highlight the critical role of improving both technical and service aspects of the application to enhance user satisfaction and loyalty in the context of digital public services.